A detailed experimental study of the validity and applicability of slotted stand-off layer rail dampers in reducing railway vibration and noise. Issue 4 (December 2018) - Zhao, Caiyou; Wang, Ping; Yi, Qiang; Sheng, Xi; Lu, Jun
This paper is concerned with an experimental study of improved slotted stand-off layer rail dampers in reducing railway vibration and noise. To achieve the goal, based on the idea of molecular design, polyurethane/vinyl ester resin interpenetrating polymer network damping materials with high damping properties was developed in the laboratory for the material of the damping layer. The effects of vinyl ester resin and organic small molecule hybridization on the damping properties of the polyurethane/vinyl ester resin interpenetrating polymer network material were investigated. The structural style of the damper was improved for ease of installation and removal in situ. Then, these improvements of damping material and structural style were used to make optimized slotted stand-off layer dampers, which were applied in a test section. The measurements indicate that the structural style improvement could improve the application convenience while also maintaining the noise reduction effect. The improved rail dampers could greatly increase the track decay rate at frequencies above 100 Hz and reduce noise levels by up to 6 dB at the speed of 60 km/h.